Multiomics profiling Identifies MCMBP as a prognostic biomarker and a potential immune-related target in pancreatic ductal adenocarcinoma via the JAK–STAT3 pathway - Zhang, Xinghai; Ma, Jiaqi; Yuan, Hao; Li, Yuzhuo; Wang, Yixin; Chen, Yujia; Zhang, Lei; Li, Fangxuan; Ma, Xi; Li, Bixuan; Xu, Wen; Wang, Yang (Frontiers in Immunology, 2025)
BackgroundMicrochromosome maintenance protein-binding protein (MCMBP) is aberrantly expressed in cancers and proposed as a diagnostic marker and therapeutic target, but its role in pancreatic ductal adenocarcinoma (PAAD) remains unclear.MethodsWe performed a comprehensive analysis of MCMBP in PAAD using multi-omics data resources, including TCGA, GTEx, CPTAC, GEO, GDSC, TIDE, HPA, MethSurv, DiseaseMeth, and LinkedOmicsKB. We examined its prognostic characteristics, epigenetic alterations, immune infiltration, immunotherapy response, and drug sensitivity. By integrating transcriptomic, proteomic, and phosphoproteomic data, we explored the biological functions and pathways of MCMBP. Sensitive drugs related to MCMBP were identified through the GDSC and Connectivity Map (CMap) drug libraries, with further functional insights obtained through GO and KEGG enrichment analyses. Potential mechanisms were investigated via gene functional experiments, phos-phorylation site predictions from LinkedOmicsKB, and protein expression validation.ResultsPan-cancer analysis revealed that MCMBP overexpression correlates with poor prognosis, including in PAAD. Cox regression identified MCMBP as an independent prognostic factor for PAAD. Low DNA methylation and high m6A modification of MCMBP may promote PAAD progression and correlate with adverse prognosis. Ge-ne function and immune infiltration analyses indicated that high MCMBP expression is closely associated with immune-related pathways, tumor cell proliferation, survival, and immune cell differentiation, and may promote Treg accumulation and immune ch-eckpoint upregulation. PAAD patients with low MCMBP expression exhibited greate-r sensitivity to anti-PD-L1 immunotherapy, suggesting a potential synergistic effect o-f MCMBP expression with anti-PD-L1 treatment. High MCMBP expression was ass-ociated with sensitivity to Gemcitabine combined with Paclitaxel, as well as small mo-lecules such as Tozasertib and Motesanib. MCMBP knockdown inhibited PAAD cell proliferation, migration, invasion, and G1-S transition. Immunohistochemical results s-howed that high MCMBP expression correlated with elevated PD-L1 levels and redu-ced CD4+ T cell infiltration in PAAD, which significantly associated with poor prog-nosis. MCMBP modulated PD-L1 through activation of the JAK-STAT3 signaling pat-hway, thereby promoting PAAD progression.ConclusionsOverexpression of MCMBP may serve as a prognostic biomarker and p-otential therapeutic target in PAAD. It drives PAAD progression by activating the JAK-STAT3 pathway to upregulate PD-L1.